Penerapan Test Driven Development (TDD) pada Laravel Menggunakan PHPUnit - Wijanarko, Sigit; Subhiyanto (LPPM STMIK ANTAR BANGSA, 2024)
Test Driven Development (TDD) is a software development approach that prioritizes writing tests before functional code. Laravel, as one of the popular PHP frameworks, provides strong support for TDD through tools like PHPUnit and Laravel Dusk. This journal discusses the concept of TDD, its benefits and challenges, and its application in developing applications with Laravel. A simple case study will also be provided to illustrate the implementation of TDD in Laravel.